Effects of power lines on habitat use and demography of greater sage‐grouse (Centrocercus urophasianus). Issue 1 (23rd October 2018) - Gibson, Daniel; Blomberg, Erik J.; Atamian, Michael T.; Espinosa, Shawn P.; Sedinger, James S.
ABSTRACT: Energy development and its associated infrastructure, including power lines, may influence wildlife population dynamics through effects on survival, reproduction, and movements of individuals. These infrastructure impacts may be direct or indirect, the former occurring when development acts directly as an agent of mortality (e.g., collision) and the latter when impacts occur as a by‐product of other processes that are altered by infrastructure presence. Functional or numerical responses by predators to power‐line corridors are indirect impacts that may suppress demographic rates for certain species, and perceived predation risk may affect animal behaviors such as habitat selection. Greater sage‐grouse ( Centrocercus urophasianus ) are a species of conservation concern across western North America that may be affected by power lines. Previous studies, however, have not provided evidence for causal mechanisms influencing demographic rates. Our primary objective was to assess the influence of power lines on multiple sage‐grouse vital rates, greater sage‐grouse habitat selection, and ultimately greater sage‐grouse population dynamics. We used demographic and behavioral data for greater sage‐grouse collected from 2003 to 2012 in central Nevada, USA, accounting for sources of underlying environmental heterogeneity. We also concurrently monitored populations of common ravens ( Corvus corax ), a primary predator of sage‐grouse nests and young. We focused primarily on a single 345 kV transmission line that was constructed at the beginning of our study; however, we also determined if similar patterns were associated with other nearby, preexisting power lines. We found that numerous behaviors (e.g., nest‐site selection, brood‐site selection) and demographic rates (e.g., nest survival, recruitment, and population growth) were affected by power lines, and that these negative effects were predominantly explained by temporal variation in the relative abundance of common ravens. Specifically, in years of high common raven abundance, avoidance of the transmission line was extended farther from the line, re‐nesting propensity was reduced, and nest survival was lower near the transmission line relative to areas more distant from the transmission line. Additionally, we found that before and immediately after construction of the transmission line, habitats near the footprint of the transmission line were generally more productive (e.g., greater reproductive success and population growth) than areas farther from the transmission line. However, multiple demographic rates (i.e., pre‐fledging chick survival, annual male survival, per capita recruitment, and population growth) for groups of individuals that used habitats near the transmission line declined to a greater extent than for individuals using habitats more distant in the years following construction of the transmission line. These decreases were correlated with an increase in common raven abundance. The geographical extent to which power lines negatively influence greater sage‐grouse demographic processes was thus contingent on local raven abundance and behavior. In this system, we found that effects of power lines, depending on the behavior or demographic rate, extended 2.5–12.5 km, which exceeds current recommendations for the placement of structures in areas around sage‐grouse leks. Nests located 12.5 km from the transmission line had 0.06 to 0.14 higher probabilities of hatching in years of average to high levels of raven abundance, relative to nests located within 1 km of the transmission line. Similarly, leks located 5 km from the transmission line had 0.02 to 0.16 higher rates of population growth (λ) in years of average to high levels of raven abundance, relative to leks located within 1 km of the transmission line. Our finding that negative impacts of the transmission line were associated with common raven abundance suggest that management actions that decouple this association between common raven abundance and power lines may reduce the negative indirect impacts of power lines on greater sage‐grouse population dynamics. However, because the removal of common ravens or the use of perch deterrents on power lines has not been demonstrated to be consistently effective in reducing common raven predation rates on greater sage‐grouse nests, we recommend preferential treatment to mitigation strategies that reduce the number of elevated structures placed within 10 km of critical greater sage‐grouse habitat. © 2018 The Wildlife Society. Abstract : Positive associations between common raven abundance and power lines resulted in reduced use of, and reproductive success in, habitat near power lines for greater sage‐grouse in central Nevada. Management actions that effectively decouple the association between common raven abundance and power lines may reduce the negative indirect impacts of power lines on greater sage‐grouse population dynamics.